The Effectiveness of Cake Application Toward Students’ Vocabulary Mastery at Eleventh Grade Students of SMA N 8 Jambi City - Marta Tambunan; Khidayatul Munawwaroh; Siti Aisyah (JELT: Journal of English Language Teaching, 2023)
The purpose of this study was to find out whether the use of the cake application was effective in increasing the vocabulary of class XI students at SMA N8 Jambi City. This study used a quantitative method with a population of 184 students in class XI, with a sample of 36 students in class XI IPA 1 and 37 students in XI IPA 2 who were selected by cluster sampling. In this study, data were collected using the pre-test and post-test to see the average score of the two classes using SPSS version 29. The results of this study indicate that (1) vocabulary mastery in using the cake application in the treatment class with an average of 80 .25; (2) Vocabulary mastery in the control class with an average of 70.92; (3) the vocabulary mastery of the treatment class students using the cake application was higher than the control class with a Sig. 0.001 > 0.05. The use of the cake application is effective in increasing the vocabulary of class XI students at SMA N8 Jambi City.